Perlindungan Hukum Terhadap Konsumen Yang Tidak Menerima Produk Pembelian Jasa Titip (Jastip) Berupa Tiket Konser Melalui Media Twitter Ditinjau Dari Hukum Positif Dan Hukum Islam - Cholqi Choirunnisa; Nisbati Sandiyah Humaeroh; Rahma Eka Fitriani (Hakim, 2023)
The Criminal Code (KUHP) regulates several forms of theft committed against property. The crime of fraud is defined in Articles 378 to 395 of Chapter XXV of the Penal Code, which further classifies different types of fraud into more nuanced categories. This type of theft, known as "criminal fraud," is a serious crime that occurs frequently. Fraud crimes can affect all levels of society and can be committed at all social levels, from the lowest to the highest. The crime of criminal fraud arises from the offender's reliance on the trust of others, and succeeds when the offender has the right opportunity and conditions to capitalize on that trust. The financial penalty for those who commit financial fraud is also set at four years in prison. In contrast, perpetrators of this type of crime are not subject to specific regulations in Islamic law. However, the main question that arises from this research is how the liability of perpetrators of financial fraud crimes according to Islamic law and positive law. The purpose of this research is to find out the rules and penalties associated with this type of fraud, as well as how Islamic law treats this type of dishonesty. The research for this article was conducted by searching for relevant information in academic journals and reference books. Meanwhile, the data collection method was conducted using the cryptanalysis method. The results show that Islamic law relating to the crime of fraud falls under the category of ta'zir. This ta'ziri law can be in the form of imprisonment, flogging, stoning, flogging, cutting hands, beheading, and stoning. Laws codified in Islamic law are more likely to achieve the intended goals of fostering social order and preventing widespread chaos.